Islamic Legal Hermeneutics and Scientific Knowledge: Reinterpreting Classical Qur’anic Exegesis in Contemporary Contexts - Mohamad Yusuf Ahmad Hasyim; Muhammad Azam; Kefah Kamel Ahmad Abuhannoud; Houthefa Salah Abdol Fattah Al Khalidi; Mohammad Ahmad Taher Ghuzlan; Yousef Ahmad Moh’d Badawi (PT. Islamic Research Publiser, 2026)
This study examines the relationship between classical Qur’anic exegesis (tafsīr) and contemporary scientific knowledge by developing an Islamic legal-hermeneutical framework that reconciles inherited exegetical interpretations with established scientific findings without compromising the normative authority of the Qur’an. Existing scholarship has predominantly relied on scientific miracle (iʿjāz ʿilmī) narratives or broad harmonisation approaches, yet has offered limited methodological guidance grounded in the principles of uṣūl al-fiqh and uṣūl al-tafsīr. Accordingly, this research aims to formulate a systematic interpretive model capable of addressing scientific developments while maintaining textual fidelity, linguistic coherence, and juristic consistency. The study employs qualitative doctrinal legal research using an Islamic legal-hermeneutical approach. Primary sources include the Qur’an, authoritative classical tafsīr literature, foundational works of uṣūl al-fiqh and uṣūl al-tafsīr, together with contemporary scientific scholarship. Data are analysed through textual, contextual, comparative, thematic, and linguistic-semantic methods to evaluate the interaction between scriptural interpretation and scientific knowledge. The findings reveal that most apparent contradictions between classical exegesis and contemporary science originate from historically conditioned human interpretations rather than from the Qur’anic text itself. By integrating contextual interpretation (siyāq), reconciliation (jamʿ), legal preference (tarjīḥ), and semantic analysis, the proposed framework enables reinterpretation of scientifically related verses in ways that remain faithful to Islamic legal methodology while accommodating validated scientific knowledge. The study further demonstrates that Islamic legal hermeneutics provides a more balanced and methodologically rigorous alternative to both literalist and purely scientistic readings of the Qur’an. Its principal contribution lies in establishing a comprehensive interpretive model that integrates uṣūl al-fiqh and uṣūl al-tafsīr into a coherent framework for religion–science dialogue, strengthening contemporary Islamic legal theory and offering practical methodological guidance for fatwā institutions in addressing emerging scientific and technological issues.